FUNCTIONING OF THE NETWORK OF UNDERGROUND GAS STORAGES IN THE CONTEXT OF THE COUNTRY'S ENERGY SECURITY (Economic journal of Lesya Ukrainka Volyn National University, 2019)
In this article the peculiarities of functioning of the underground network of gas storages of Ukraine in the context of energy security were investigated. The organizational and economic basis of energy security of the State against the functioning of the network of gas storages of the state is outlined. A review of the theoretical approaches to understanding the concept of "energy security" and by systematization a wide range of concepts is given unified definition of this concept. A review of the theory of Practice of operation of gas underground storage facilities, which is an important element in ensuring energy security of European countries, as well as the formation of favourable transit potential. Using a systematic approach, analysis of the grassroots of legislative documents, as well as the history of the formation of gas storage tanks, was concluded that they can become integral components in the network interaction between supply and storage channels Of gas in the geopolitical space towards reforming the liberalized gas market. Whereas geographical affinity and mostly accumulation of necessary network gas resources and as a result of empirical analysis it was possible to trace energy dependence of many countries of Europe from the gas reserve balance of our country. Originality of the research is the substantiation of theoretical hypotheses concerning the main factors and tendencies of geopolitical policy of adapting the spatial networks of supply and storage of gas resources in the context of the liberalized gas market. To implement the gas reform and equality of Ukraine in the European gas market, reforms should be implemented in the interests of Ukrainian citizens, providing high-quality and reliable services, while harmonizing the competitive environment between owners of Efficient gas companies. Due to the adoption of the Law on the natural gas market in 2015, the legal plane of Ukraine significantly drew closer to the EU energy legislation. At the end of the reform, it is early to say, as there are important steps ahead to create a transparent environment of an independent regulator that avoids monopoly pressure in the gas market, limit political-oligarchic lobbying and Boost investment in the specified sector. One of the most important aspects of the effectiveness of the marked steps is the significant transit potential of Ukraine, which is in a certain way based on the presence of significant reserves of underground storage of gas storages, which in turn raise national independence and Security of our country. The purpose of the publication is to light the theoretical and practical knowledge about the underground gas storages of Ukraine with the finding out of their role and importance in the energy security of the geopolitical space. The main tasks, which reveal the meaning of the specified purpose, should be noted: the historical ages of the network of gas storages; Concentration and peculiarities of gas storages functioning in Ukraine; Interaction and mutual consistency of gas tanks with European gas channels; Problematic issues that hinder the uninterrupted and safe gas supply; Place and function of the gas storage network in the context of national and European security.
Keywords: Network of gas resources, energy security, liberalized market, reforming, energy independence, underground storages, gas storage